Determinan Audit Delay pada Perusahaan Manufaktur Sektor Aneka Industri yang Terdaftar di Bursa Efek Indonesia tahun 2020-2022 - Kumala Sari, Dewi; Djamil, Nasrullah (MUI Kota Pekanbaru, 2024)
This study is a quantitative study that aims to determine how the influence of managerial ownership, institutional ownership, the proportion of independent commissioners, the number of audit committees, and the board of directors on audit delay in various industrial sector manufacturing companies listed on the Indonesia Stock Exchange in 2020-2022. The number of samples in this study were 20 companies with a sample withdrawal method using purposive sampling method, this study uses secondary data obtained from the Indonesia Stock Exchange. The data analysis tool uses eviews 12. While the data processing method used is panel data regression analysis. The partial hypothesis research results show that the institutional ownership variable and the board of directors have a significant effect on audit delay. Meanwhile, the managerial ownership variable, the proportion of independent commissioners, and the number of audit committees have no significant effect on audit delay. The results of hypothesis research simultaneously have a significant effect on audit delay. The result of the coefficient of determination value adjust r-squared (R2) is 0.997220, this shows that the contribution of all independent variables in explaining the dependent variable is 99.72%.